Privatising Pensions in the UK: How to Restore Contracting Out. (June 2014) - Booth, Philip; Niemietz, Kristian
Abstract For much of the post‐war period in the UK, individuals were allowed to use private pension provision to replace part of their state pension. This system was supported by all political parties but it has been eroded since the 1990s. The opportunity to 'contract out' of the state pension is finally being abolished by the current Conservative/Liberal Democrat coalition government. This paper proposes a new method of allowing people to contract out of the state pension system, calculates appropriate rebates of social security taxes and discusses the potential risks of adopting the proposals.